2007
DOI: 10.1074/jbc.m610725200
|View full text |Cite
|
Sign up to set email alerts
|

HNF1α Inactivation Promotes Lipogenesis in Human Hepatocellular Adenoma Independently of SREBP-1 and Carbohydrate-response Element-binding Protein (ChREBP) Activation

Abstract: Biallelic inactivating mutations of the transcription factor 1 gene (TCF1), encoding hepatocyte nuclear factor 1␣ (HNF1␣) were identified in 50% of hepatocellular adenomas (HCA) phenotypically characterized by a striking steatosis. To understand the molecular basis of this aberrant lipid storage, we performed a microarray transcriptome analysis validated by quantitative reverse transcription-PCR, Western blotting, and lipid profiling. In mutated HCA, we showed a repression of gluconeogenesis coordinated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
95
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 34 publications
5
95
0
Order By: Relevance
“…We also found a silencing of L-FABP, which encodes liver fatty acid binding protein 1, suggesting that impaired fatty acid trafficking may also contribute to the fatty phenotype. We showed that absence of L-FABP staining in HCA was specific to HNF1α inactivation among the different benign liver tumor subtypes (82,87). Together this indicates that steatosis, frequently observed in HCA, may contribute to tumorigenesis, and this occurs through a constant and specific mechanism in the HNF1α inactivated tumor subtype.…”
Section: A-hnf1α Inactivationmentioning
confidence: 57%
See 1 more Smart Citation
“…We also found a silencing of L-FABP, which encodes liver fatty acid binding protein 1, suggesting that impaired fatty acid trafficking may also contribute to the fatty phenotype. We showed that absence of L-FABP staining in HCA was specific to HNF1α inactivation among the different benign liver tumor subtypes (82,87). Together this indicates that steatosis, frequently observed in HCA, may contribute to tumorigenesis, and this occurs through a constant and specific mechanism in the HNF1α inactivated tumor subtype.…”
Section: A-hnf1α Inactivationmentioning
confidence: 57%
“…Furthermore, we identified a repression of gluconeogenesis coordinated with an activation of glycolysis, citrate shuttle and fatty acid synthesis, which predicted elevated rates of lipogenesis in HCA tumors harboring mutations in HNF1α (87). In these tumors, lipid composition was dramatically modified and, surprisingly, lipogenesis activation did not operate through SREBP-1 and ChREBP, both of which instead were repressed.…”
Section: A-hnf1α Inactivationmentioning
confidence: 91%
“…3,4 This steatosis results from the activation of lipogenesis. 5 Steatosis is also observed in other subtypes of HCA, but less frequently and to a lesser degree. Thus, no lesion without HNF-1␣ inactivation shows such a diffuse distribution of fat, although foci of steatosis may be observed in inflammatory HCA.…”
Section: Discussionmentioning
confidence: 94%
“…5 Liver fatty acid binding protein (L-FABP), which encodes L-FABP 1, has also been shown to be silenced in these tumors, suggesting that impaired fatty acid trafficking may also contribute to the fatty phenotype of HNF-1␣-inactivated HCA.…”
mentioning
confidence: 99%
“…LFABP is a downstream target of HNF1-α 13 and bialellic loss of HNF1-α is associated with loss of LFABP expression, an observation that forms the foundation for using LFABP immunohistochemistry as a diagnostic tool. 14 It is unknown how the loss of the tumor suppressor HNF1-α contributes to neoplasia, but biallelic loss of HNF1-α can lead to activation of glycolysis and lipogenesis, 15,16 as well as upregulation of ERBB2 and mTOR. Other possible targets include upregulation of cyclin D1 to promote cell division and upregulation of PDGFA and PDGFB, facilitating angiogenesis.…”
Section: Discussionmentioning
confidence: 99%